Perception of journalists about disinformation and professional routines in the digital age - Montemayor Rodríguez, Nancy; García Jiménez, Antonio (Revista General de Información y Documentación, 2021)
Disinformation is a reality that affects society in general and journalism and the media in particular. The role of professionals in this field is generally recognized. To get to know it better, this article looks at the perception that a sample of journalists has about the phenomenon and about professional routines in the digital age. Twelve structured interviews were conducted. Of these, ten to general journalists from public and private news, press, radio and television companies; and two to specialists in digital verification of the two main platforms in Spain, which are also the pioneers, due to their foundation in 2018: Maldita.es and Newtral. The results show unanimity among journalists on the magnitude of the phenomenon, as well as a predominance of classic techniques to contrast information and check sources. It is worth mentioning the new phenomenon of the communities of followers with which journalists from the verification platforms have, which have involved audiences, so that these communities not only alert about unfounded rumors that arise on social networks or WhatsApp, but also they participate as specialized sources in certain areas of knowledge.
Keywords: Disinformation; journalists; professional routines; media; social networks; digital age